The man in the high garden: An epicurean virtual history - Ćirković Milan (Belgrade Philosophical Annual)
Following the lead of heterogeneous and invariably brilliant thinkers as Thucydides, Arnold J. Toynbee, Winston Churchill, Carl Sagan, Philip K. Dick, and Niall Ferguson, I consider a virtual history - or an alternative Everettian branch of the universal wavefunction - in which the ancient materialism and atomism of Epicurus (and heliocentrism of Aristarchus, for good measure) have prevailed over the (Neo) Platonist-Aristotelian religious-military complex. Such a historical swerve (pun fully intended) would have removed the unhealthy obsession with mind-body dualism and dialectics, which crippled much of the European thought throughout the last millennium. It is at least open to serious questioning whether quasireligious totalitarian ideologies could have arisen and brought about so much death, suffering and pain in this virtual history as they did in our actual history.